Introduction to counselling skills : text and activities - Nelson-Jones, Richard (London : Thousand Oaks, Calif. : SAGE, 2000)
Introduction to Counselling Skills is a textbook for use on introductory courses aimed at developing basic counselling skills." "Combining explanations, examples and activities, the book will be invaluable in a wide range of educational, voluntary and professional settings. Whether intending to work as counsellors or to use counselling skills in other professional roles, students will find this an essential source of information and guidance." "A highly experienced teacher and bestselling author, Richard Nelson-Jones demonstrates the central importance of warm and humane helping relationships and encourages students to use their hearts as well as their heads in developing their counselling skills. The book explains: what counselling skills are; how to improve listening skills; ways of clarifying and expanding understanding; changing communications, actions and thinking; how to conduct sessions; ethical issues." "Each chapter incorporates a list of intended outcomes, a summary and practical activities to help students in their learning. Numerous examples and case studies are included throughout and a glossary of terms is provided for quick reference. Introduction to Counselling Skills will encourage students to bring out the best in themselves and to develop as skilled and humane helpers."--Jacket
Includes bibliographical references and indexes.
Keywords: Counseling